Pressure-induced Glassy Networks of Enstatite (MgSiO3) and Forsterite (Mg2SiO4) - Hoang Anh, Nguyen; Son, Nguyen Hung; Van Hong, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 39 No 1DO - 10.25073/2588-1124/vnumap.4767, 2023)
This work is designed to focus on the glassy network analysis and visualizing the cluster and subnets formation, the rich set of bond-, edge- and face-sharing linkages. The correlation between the degree of polymerization and linkages forming is apparently indicated. The distribution of SiO x clusters is computed to determine the polymerization characteristic and Mg-rich region. The distribution of BOs, NBOs and FOs also are investigated to prove the behavior of Mg 2+ incorporating into the -Si-O- network. Polyhedral units, clusters, and subnets are vividly visualized so as to have a better understanding of cluster merging. Besides, in this work we have also clarified the distribution of edge-sharing and face-sharing subnets/network between Si-Si and Mg-Si species.